PENGARUH KOMPETENSI SOSIAL TUTOR TERHADAP PARTISIPASI BELAJAR WARGA BELAJAR PAKET C DI UNIT PELAKSANA TEKNIS SATUAN PENDIDIKAN NON FORMAL SANGGAR KEGIATAN BELAJAR LASINRANG KABUPATEN PINRANG - Riyanti, Riri; Natsir, Nasrah; Marzuki, Kartini (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research is a quantitative study which aims to determine the influence of tutors' social competence on the learning participation of Package C students at UPT SPNF SKB Lasinrang, Pinrang Regency. The independent variable in this research is social competence, while the dependent variable in this research is learning participation. The sample from this research was 51 people. Data collection was carried out using questionnaires and documentation methods. The techniques used in data analysis are descriptive frequency, data normality, and simple linear regression. The research results show that: (1) the social competence of tutors at UPT SPNF SKB Lasinrang is in the quite good category with a score of 74%. (2) Learning participation is in the good category with a score of 76%. (3) there is a significant or real influence between the influence of the tutor's social competence on the learning participation of package C students at UPT SPNF SKB Lasinrang, Pinrang Regency. So at UPT SPNF SKB Lasinrang we must further improve the social competence of tutors so that students can participate in the learning process.